Ethnobotanical study of medicinal flora in the Lembak Delapan Tribe Community of Jum'at Village, Talang Empat District, Central Bengkulu Regency - Sri Rahayu; Guswarni Anwar; Wiryono Wiryono (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2026)
The potential for medicinal plants in Jum'at village is significant, despite the fact that many people today do not use traditional medicine due to the convenience of purchasing pharmaceuticals at stores, accessing remedies at home, or seeking treatment at health facilities or hospitals. The study aimed to identify and assess medical plant species and the socio-cultural conditions of the Lembak Delapan tribe's flora consumption in Jum'at village, Talang Empat District, Central Bengkulu Regency. This study used snowball sampling, interviews, and village tours to collect data and identify plants by comparing their characteristics to photos in plant identification literature. The findings revealed that 53 plant species used as traditional medicine were divided into 33 groups, with 10 species being the most commonly used by the community. These were the most often planted plants, others grew naturally near the hamlet. Plant medicinal components include the entire plant or specific portions (roots, stems, leaves, and fruit) and were viewed by the community as treatments for both internal and external ailments. They were processed by boiling, pounding, direct ingestion, brewing, squeezing, and incineration. We suggest that future studies collect the most recent data on the medicinal plant kinds found in Bengkulu Province and to carry out research on the chemical composition of the discovered medicinal plants.